2019
DOI: 10.1109/tuffc.2018.2883427
|View full text |Cite
|
Sign up to set email alerts
|

Robust Short-Lag Spatial Coherence Imaging of Breast Ultrasound Data: Initial Clinical Results

Abstract: Ultrasound is frequently used in conjunction with mammography in order to detect breast cancer as early as possible. However, due largely to the heterogeneity of breast tissue, ultrasound images are plagued with clutter that obstructs important diagnostic features. Short-lag spatial coherence (SLSC) imaging has proven to be effective at clutter reduction in noisy ultrasound images. M-Weighted SLSC and Robust-SLSC (R-SLSC) imaging were recently introduced to further improve image quality at higher lag values, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…This leads to a hypothesis that adaptive beamforming may improve the visualization of the interventricular septum of the heart. We would also like to point to the results mentioned in Section 4.4 from (Wiacek et al 2018b), where we showed that the novelty and clinical relevance of adaptive beamforming is not limited to merely improving the image quality in terms of contrast and resolution. Adaptive beamforming can improve diagnostics by displaying novel clinical information different from the conventional B-mode image.…”
Section: This Thesis In a Holistic Viewmentioning
confidence: 81%
See 2 more Smart Citations
“…This leads to a hypothesis that adaptive beamforming may improve the visualization of the interventricular septum of the heart. We would also like to point to the results mentioned in Section 4.4 from (Wiacek et al 2018b), where we showed that the novelty and clinical relevance of adaptive beamforming is not limited to merely improving the image quality in terms of contrast and resolution. Adaptive beamforming can improve diagnostics by displaying novel clinical information different from the conventional B-mode image.…”
Section: This Thesis In a Holistic Viewmentioning
confidence: 81%
“…More specifically, we showed that SLSC could "improve the fluid vs. solid classification of hypoechoic breast masses and improve the detectability of fluid-filled masses, thereby improving the diagnostic power of breast ultrasound imaging." (Wiacek et al 2018b). Three images from the publication is included in Figure 4.1, where (a) is a simple fluid-filled cyst, (b) is a fibroadenoma (a benign mass) while (c) is a hematoma (a collection of blood).…”
Section: In-vivo Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps they can be better used to detect highly coherent targets, such as microcalcifications, or interfaces. Coherence beamforming has also been shown to be able to aid in the differentiation between solid and fluidfilled masses in-vivo [10].…”
Section: Discussionmentioning
confidence: 99%
“…To highlight the versatility of the DNN trained with I fds , this DNN was evaluated with a ten-frame sequence of an in vivo simple cyst surrounded by breast tissue (denoted as Cyst #2), which was originally acquired for the separate study reported in [ 45 ]. These data were acquired with focused (rather than plane wave) transmissions, using an Alpinion L8-17 linear array transducer with parameters for the acquisition listed in Table II .…”
Section: Methodsmentioning
confidence: 99%